Mendidik Anak Berdasarkan Golongan Darah - Tobing, Christine Masada Hirasita (STKIP Muhammadiyah Pringsewu, 2018)
Abstract:Â Since birth, individuals based on the blood type have formed their basic personality. Results of observations and statistical data for 40 years, mentioned there are differences between the characteristics of each blood group. Blood type is lowered by blood type of biological parents. If parents are O, chances are the child is blood type O, except AB. However, if parents AB children A bloody chance, B, AB cannot be the blood type, O. Teachers and parents are expected to understand each different character of blood type in order to maximize abilities that exist for the child.Keywords: Keywords: Blood Type, Character, Educate